Neurosyphilis with positive anti-N-methyl-D-aspartate receptor antibody: a case report - Sha, Zhu; Jing, Shi; Feng, Gao; Hongjun, Hao; Xianzeng, Liu (Frontiers in Neurology, 2023)
A case of neurosyphilis with positive anti-N-methyl-D-aspartate receptor (NMDAR) antibody-positive was reported. A 54-year-old man who presented with acute memory deficits and speech impairment was admitted to our hospital. Acute ischemic stroke (AIS) was initially considered, and he was given prescribed intravenous thrombolysis with recombinant tissue-type plasminogen activator (rt-PA). However, he still hadintermittent onset of episodic memory disorder and orientation disorder intermittentlystill occurred. There is nNo diffusion restriction on was indicated by the magnetic resonance imaging (MRI)No high signal intensity on diffusion-weighted imaging (DWI) was identified on magnetic resonance imaging (MRI) of the brain, and subclinical seizures were frequently found on by electroencephalogram (EEG). Rapid plasma reagin (RPR) test of serum in showed positive results ofserum for syphilis was positive. Analysis of cerebrospinal fluid (CSF) revealed elevated leukocyte count and protein level. RPR test, treponema pallidum particle agglutination (TPPA) assay, and treponema pallidum antibody (TP-Ab) in CSF showed positive results, and the anti-NMDAR antibodies were positive in CSF and serum. Finally, the patient was diagnosed as neurosyphilis with positive anti-NMDAR antibody-positive. The clinical symptoms were improved, and the leukocyte count in CSF was reduced after treatment with intravenous penicillin G and levetiracetam. This case suggests that in cases in whichwith positive laboratory testingresults for neurosyphilis and NMDAR antibodies are positive that, the proper treatment has to be decided on via use ofbased on all of the available clinical and diagnostic testing data. if a patient with neurosyphilis is positive for NMDA antibody which may only be a bystander, penicillin is still the mainly treatment.